Antibodies anti-Shiga toxin 2 B subunit from chicken egg yolk: isolation, purification and neutralization efficacy - Parma, Y. R. (2011)
Fil: Parma, Y. R. Instituto Nacional de Tecnología Agropecuaria. Centro Nacional de Investigaciones Agropecuarias. Instituto de Patobiología; Argentina.